2014
DOI: 10.1007/s12013-014-0378-6
|View full text |Cite
|
Sign up to set email alerts
|

AKT Pathway Affects Bone Regeneration in Nonunion Treated with Umbilical Cord-Derived Mesenchymal Stem Cells

Abstract: We have previously grafted human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) with blood plasma to treat rat tibia nonunion. To further examine the biological characteristics of this process, we applied an established hUC-MSCs-treated rat nonunion model with the addition of an inhibitor of AKT. SD rats (80) were randomly divided into four groups: a fracture group (positive control); a nonunion group (negative control); a hUC-MSCs grafting with blood plasma group; and a hUC-MSCs grafting with blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…In addition to AKT activation, we also observed increased transcript levels of AKT itself as well as other pathway-associated genes. This finding is consistent with the known interaction between AKT phosphorylation and AKT gene expression [67]. …”
Section: Discussionsupporting
confidence: 92%
“…In addition to AKT activation, we also observed increased transcript levels of AKT itself as well as other pathway-associated genes. This finding is consistent with the known interaction between AKT phosphorylation and AKT gene expression [67]. …”
Section: Discussionsupporting
confidence: 92%
“…PLT-related parameters, including platelet count, volume, mean volume and distribution width decreased post-operation compared to pre-operation. Similar results on safety have been reported in our previous study, in which we injected hUC-MSCs into rats and found hUC-MSCs located in the rat non-union area that differentiated into osteoblasts, as well as no local or systematic manifestations of toxic reactions and graft vs. host disease during and after transplantation (11,12). Based on the above results, this approach is relatively safe.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, stem cell transplantation has gradually emerged as a promising approach for the treatment of ONFH (8,16,17). In previous studies, we grafted human UC-derived MSCs (hUC-MSCs) to treat non-union in rats and human (11–13). Our results demonstrated the safety and efficacy of osteoblastic differentiation of hUC-MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Fully informed consent was obtained several weeks prior to delivery. HUC-MSC were isolated and propagated as previously described (10–13). UCs were filled with 0.1% collagenase (Sigma-Aldrich, St. Louis, MO, USA) in PBS and incubated at 37°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, MSCs can be isolated from bone marrow, umbilical cord (UC) blood, and connective tissue (Wharton's jelly) (9), and can be expanded in culture to use as a source of stem cells to elicit cardiac repair. In previous studies, we investigated the safety and efficacy of human UC-MSCs (HUC-MSCs) in rat (10–12) and human bone non-union (13). …”
Section: Introductionmentioning
confidence: 99%